HARMONI MASYARAKAT TRADISI DALAM KERANGKA MULTIKULURALISME - Hadi Cahyono, Ardhana Januar Mahardhani dan (ASKETIK, 2017)
Society in this era can be said as the modern society with anything life sufficiency that is very easy to be gotten,but there are still many societies that have not been release with their tradition that have been happenedlong time before they are birth. Existence and continuance activities of tradition element, such as like in Javaculture which is known as count the day activity before the wedding held, salvation whether for baby bornor dead, home construction, precisely this activities that bring the diversity in the multiculturalism element.Multiculturalism itself is recognition if there are different cultures but they are still can life and develop withinthe similar environment without loss on either side. That thing becomes the basic of this article writing. Tryingto watch the difference is natural things in the multiculturalism framework.Keywords: society, tradition, multiculturalism.